Interlaboratory Study of the Standard Test Method for Evaluating Bond of Seven-Wire Steel Prestressing Strand - Polydorou, Thomaida; Riding, Kyle A.; Peterman, Robert J. (My University, 2016)
As part of a study to determine minimum acceptance criteria for strand bond as measured using ASTM A1081, ruggedness and interlaboratory studies were conducted on ASTM A1081 to determine the test method coefficient of variation. Based on the ruggedness study, a modified method of ASTM A1081 was proposed that changes the mortar flow requirements from 105% to 120%, standardizes the sand source and gradation, fixes the water-cement ratio at 0.45, and eliminates the time window. The interlaboratory study was performed using ASTM A1081 and the modified ASTM A1081 method on three different strand sources. ASTM A1081 had an average coefficient of variation in the interlaboratory study of 14.5% and 11% for the modified method.
Keywords: ASTM A1081